Car Antifreeze and Coolant: Comparing Water and Ethylene Glycol as Nano Fluid Base Fluid - Kimulu, Ancent Makau; Mutuku, Winfred Nduku; Mutua, Nicholas Muthama (My University, 2018)
Most internal combustion engines are fluid cooled using liquid coolants mostly water and ethylene glycol, whose heat transfer capabilities are limited. An alternative for improving their thermophysical properties is the addition of metal oxides so as to make Nanofluids. This study investigates car antifreeze and coolants by comparing water-based and ethylene glycol based Nanofluids to determine the Nanofluid which provides optimum cooling. The governing equations are non–dimensionalised using similarity transformation and the resulting equations solved numerically using the Runge–Kutta fourth order scheme. Graphical results of pertinent parameters on fluid velocity, temperature, skin friction and rate of heat transfer are presented and discussed in depth putting into consideration the industrial application. It was observed that the magnetic field slows the fluid flow while increasing the fluid temperature. Also ethylene glycol Nanofluid offers better cooling capabilities
Keywords: Nano-fluid; Antifreeze; Runge-Kutta; Coolant.